Editors’ Notes - Worrall, Amy; Wanniarachige, Dane (Trinity Student Medical Journal, 2020)
This year marked the twentieth anniversary since the founding of the Trinity Student Medical Journal in 1999 under the guidance of Professor Conleth Feighery and Professor Moira O’Brien. The vast progress made in publication, education and research since then and the speed at which research makes it from the bench to print (with early releases online) and then to the patient’s bedside is phenomenal. The TSMJ has been on a journey involving twenty committees, and a mix of conferences, study days, poster competitions, medical art awards, interviews, publication crash courses and journal clubs throughout its time. It has always delivered with physical journal copies being ferried to libraries, lecture theatres and the Trinity College teaching hospitals, as well as the legal deposit libraries. This years journal highlights some interesting and topical articles; Hazeem Ahmayuddin’s case report (completed during an elective) on the management of a primary small cell carcinoma in the subglottis highlights a rare condition, and discusses the urgent need for further trials in the area, and Fátimah Alaya’s feature article on the reach of the GDPR that highlights and reflects on the limbo experienced in healthcare research for the last two years. There are two comprehensive reviews; one on the current research in the prodromal phases of Alzheimer’s Disease by Tristram Ryan, and the other on the balance between cost and efficacy of the new immune checkpoint inhibitor drugs in cancer therapeutics by now final year student Michael McKenna. And there are many other fascinating reads on reproductive rights, audits based in general practice, palliative care research and approaches and the need to sedating children during MRI studies. As medicine evolves rapidly, so too does the world of publishing. We are evolving too in the TSMJ and are moving towards online platforms for that last few years. While print editions are key, accessibility and relevance of research relies on online presence and we too must move with the times. Our new website using the Open Journal Systems is soon to go live and will revolutionise the submission process and the ease with which the journal can be accessed, dispersed and referenced. We are delighted to continue to provide a platform for students in medicine, dentistry and health science fields to publish their research, reviews, case reports and academic efforts that they devote their time to during their undergraduate studies. We are also student run which means that the entire production is a culmination of hard work and volunteered time by students from first year through to final year that are giving of their time and energy to foster others, teaching through editing, providing through production, learning through guiding others and yourself to deliver a product as a team. The journal would not be here without students to research, authors to write, editors to review, designers to produce, and the numerous researchers, consultants and academics that together support student ventures. We are deeply grateful to all those involved in the Trinity Student Medical Journal, this year, and for every year that has gone before us. We are pleased to present you with the twentieth edition of the Trinity Student Medical Journal. The topics are varied, thought-provoking and are produced by the talent of the upcoming health scientists, dentists and doctors. We are proud as ever to continue to serve as a platform for student research, student editorial work and student collaboration. Thank you to all our sponsors, supporters, and the School of Medicine for the constant support.